Respuesta :
Answer:
x = 8
Step-by-step explanation:
Given equation:
[tex]\dfrac{-2}{3} (x+12)+\dfrac{2x}{3} =\dfrac{-5x}{4} +2[/tex]
Start out by simplifying the distributive property on the left hand side.
[tex]\implies \dfrac{-2x}{3} + \dfrac{(-24)}{3} +\dfrac{2x}{3} =\dfrac{-5x}{4} +2[/tex]
Combine like terms on the left hand side.
[tex]\implies x\huge\text{(}\dfrac{-2}{3} + \dfrac{2}{3}\huge\text{)}+ \dfrac{(-24)}{3} =\dfrac{-5x}{4} +2[/tex]
Simplify the left hand side.
[tex]\implies x\huge\text{(}0\huge\text{)}+ \dfrac{(-24)}{3} =\dfrac{-5x}{4} +2[/tex]
[tex]\implies x\huge\text{(}0\huge\text{)} - 8 =\dfrac{-5x}{4} +2[/tex]
[tex]\implies0- 8 =\dfrac{-5x}{4} +2[/tex]
[tex]\implies-8 =\dfrac{-5x}{4} +2[/tex]
Subtract 2 both sides.
[tex]\implies-8 -2 =\dfrac{-5x}{4} +2 - 2[/tex]
[tex]\implies-10 =\dfrac{-5x}{4}[/tex]
Use cross multiplication.
[tex]\implies-10 \times 4 =-5x[/tex]
[tex]\implies-40 =-5x[/tex]
Divide -5 both sides.
[tex]\implies \dfrac{-40}{-5} =\dfrac{-5x}{-5}[/tex]
[tex]\implies 8=x[/tex]
Thus, the value of x is 8.
Answer:
x = 8
Step-by-step explanation:
Given equation:
[tex]-\dfrac23(x+12)+\dfrac23x=-\dfrac54x+2[/tex]
Multiply both sides by 3:
[tex]\implies -2(x+12)+2x=-\dfrac{15}{4}x+6[/tex]
Multiply both sides by 4:
[tex]\implies -8(x+12)+8x=-15x+24[/tex]
Expand brackets:
[tex]\implies -8x-96+8x=-15x+24[/tex]
Combine like terms:
[tex]\implies -96=-15x+24[/tex]
Add 15x to both sides:
[tex]\implies 15x-96=24[/tex]
Add 96 to both sides:
[tex]\implies 15x=120[/tex]
Divide both sides by 15:
[tex]\implies x=8[/tex]